Modeling the Minimum Temperature Change of Hun Station for the Period 1961-2099 Using SDSM Technology (Libya Journal of Geographical Studies, 2025)
The research aims to predict the difference and percentage of change in the minimum temperature for the period (2011-2099) based on the daily minimum temperature data observed at the Hun station for the base period (1961-1990 AD) using the Statistical Downscaling Madel (SDSM) technique according to the climate change scenarios (B2a) (A2a), which are scenarios approved by the Intergovernmental Panel on Climate Change (IPCC) in a report known as SRES for the year 2000 AD to make climate and environmental forecasts. The data were divided into three projected periods (2011-2040 AD) (2041-2070 AD) (2071-2099 AD).The results of the study showed that there is a variation in the difference and percentage of change in the minimum temperature during the modeling periods (2011-2099 AD) from one month to another, from one period to another, and from one scenario to another with respect to the base period.
Keywords: Climate change; Minimum temperature; Climate scenarios; Statistical Minimization Model (SDSM).